Four new species and an identification key for Stygodesmodora Blome, 1982 (Nematoda: Spiriniinae) from the continental shelf off northeastern Brazil - Larrazábal-Filho, Alexandre L.; Neres, Patrícia F.; Esteves, André M. (Zootaxa, 2017)
Four previously undescribed species of marine nematodes were collected on the continental shelf of the Potiguar Basin in northeastern Brazil. Stygodesmodora amphidialis sp. n. has a large fovea amphidialis, long cephalic setae, globular spermatic cells, 6–8 tubular supplements and button-like caudal papillae. Stygodesmodora paramphidialis sp. n. is similar but can be differentiated by the presence of a bipartite lumen and a fovea amphidialis smaller than in S. amphidialis sp. n. Stygodesmodora robusta sp. n. has a relatively robust body, strongly annulated cuticle, one large dorsal tooth and a small ventral tooth, one row of nine ventrally placed precloacal setae, and arched spicules. Stygodesmodora potiguensis sp. n. has the cuticle strongly annulated, many setae along the body, supplements absent, and sexual dimorphism in the size of the fovea amphidialis. These four new species increase to seven the number of taxa known in the genus.